PENGARUH KOMUNIKASI RISIKO DAN SIKAP MASYARAKAT TERHADAP MITIGASI BENCANA SEMBURAN GAS DI KOTA PEKANBARU - Hanshardi, Muhammad (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
Environmental and communication issues are interrelated and have a significant impact on each other. Communication plays an important role in how we understand, convey and respond to environmental issues. Remembering the risks that a disaster can cause not only in the form of property loss, but also environmental damage and loss of life. The main aim of risk communication is to increase individual or community understanding, awareness and preparation of existing risks. The aim of this study is to analyze the influence of risk communication and community attitudes towards disaster mitigation in Pekanbaru City. This research is quantitative research involving 375 respondents. The results of this research show that the partial test results for the risk communication variable on disaster mitigation are sig. 0.011 < 0.05, where the risk communication variable influences disaster mitigation. In the partial test the community attitude variable does not influence disaster mitigation, this is because the partial test result on this variable is sig. 0.133 > sig.0.05. Based on the results of the simultaneous test or F test which was carried out, the influence between the independent variables simultaneously and the dependent variable was 3.292, where the value in the F test was greater than the t table test, namely 0.098. Key Words: Risk Communication, Community Attitudes, Natural Gas Burst Disaster, Pekanbaru City.